Thyroid dysfunction in Turkish patients with chronic hepatitis C receiving peginterferon plus ribavirin in the period of 2005-2010 - Barut,Sener (2012)
Interferon-α based therapy for chronic hepatitis C (CHC) is associated with thyroiditis and thyroid dysfunction (TD). This study investigated whether TD during pegylated interferon-a (PEG-IFN) plus ribavirin treatment favors sustained viral response (SVR), and also the association between TD and PEG-IFN formulations. This retrospective study was performed in CHC patients who had received PEG-IFN plus ribavirin and had been followed for six months after treatment. Several factors were compared between patients with and without TD. 119 patients were included in the study. De novo incidence of TD was found to be 16.8%, and 16 of the 18 patients with TD achieved SVR. Although this rate was higher than patients without TD according to univariate analysis, logistic regression analysis revealed that there was not a significant association between TD and SVR, whereas baseline thyroperoxidase antibody (anti-TPO) positivity was the only significant predictor of TD. Moreover, TD was not associated with PEG-IFN type. Both interferon-a and hepatitis C virus (HCV) contribute to TD during antiviral therapy. It seems that there is no association between thyroid toxicity and viral clearance or type of PEG-IFN; however, anti-TPO positivity before treatment is the strongest predictor for TD during antiviral therapy.